Thermodynamic analysis of 100% system fuel utilization solid oxide fuel cell (SOFC) system fueled with ammonia. (1st December 2021) - Selvam, Kalimuthu; Komatsu, Yosuke; Sciazko, Anna; Kaneko, Shozo; Shikazono, Naoki
Graphical abstract: Highlights: Feasibility of 100% system fuel utilization SOFC system fed with NH3 is studied. 100% fuel utilization is achieved by operating SOFC in dead-end anode (DEA) loop. System efficiency as high as 75% LHV can be achieved with NH3 fed DEA loop SOFC. The energy and exergy balance studies are conducted and compared with standard SOFC. Parametric analyses of critical operating parameters of the DEA system are studied. Abstract: The system efficiency of solid oxide fuel cells (SOFCs) fueled with ammonia or pure hydrogen always underperforms compared to the SOFCs fueled with carbon-based fuels. Hence, improving the efficiency of SOFCs fueled with pure hydrogen or hydrogen carriers such as ammonia is required to promote hydrogen economy. This study deals with the thermodynamic analyses of SOFC with 100% system fuel utilization configuration achieved by a dead-end anode (DEA) loop. The results are compared with the conventional SOFC configuration with the afterburner setup. It is shown that the energy efficiency and exergy efficiency of ammonia-fueled recirculation system are 12.17% points and 11.39% points higher than the conventional system. Energy balance comparison shows that the reduction in heat loss through exhaust gas is one of the significant factors for improving the system efficiency. The improvement in the exergy efficiency of the recirculation system is attributed to the reduction in exergy destructions in air preheaters and the elimination of exergy destruction at the afterburner. In addition, a parametric analysis and artificial neural network– genetic algorithm (ANN-GA) based optimization are performed to understand the effects of stack fuel utilization, current density, stack operating temperature, radiation loss, the pressure ratio across the membrane, and species removal rate in anode off-gas on system efficiency. The system efficiency as high as 75% lower heating value (LHV) can be achieved by the DEA loop configuration with operating the system at lower stack fuel utilizations.